The Effect Of Entrepreneurship Education In The Universities Of Cali (2002)
Entrepreneurial Education started in Cali Colombia in 1976 at the Universidad del Valle (Industrial Engineering Program) and at the Universidad ICESI in 1979. Since then the idea has expanded to several programs in the previously mentioned universities as well as others. In 1991 – 1992 several research projects were conducted to find out the effect of entrepreneurial education in Icesi’s alumni. In the 1999 – 2000 period, a new research project was launched to measure the effect of entrepreneurial education in six under graduate academic programs in three of Cali´s universities